Adsorption of Congo red Dye from Aqueous Solution onto Wheat Husk in a Fluidized Bed Reactor - Sabah, Israa; I. Alwared, Abeer (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
The purpose of this paper is to examine absorbance for the removal of the Red Congo using wheat husk as a biological pesticide. Several experiments have been conducted with the aim of configuring breakthrough data in a fluidized bed reactor. The minimum fluidized velocities of the bed were found to be 0.031 mm/s for mish sizes of (250) µm diameter with study the mass transfer be calculated KL values. The results showed a well-fitting with the experimental data. Different operating conditions were selected: bed height (2, 5 and 10) cm, flow rate (90, 100and 120) ml/sec and particle diameter (250, 600, 1000) µm. The breakthrough curves were plotted for Congo Red, Values showed that the lower the bed, the lower the number of adsorbents and the potential of the weak bed to condense the density of the solution, which also increases the flow rate and will increase the mass transfer rate.